High protein-sorghum grain as the only protein source in an all concentrate steer finishing ration - Smith, E.F.; Richardson, D.; Deyoe, C.W. (Kansas Agricultural Experiment Station, 2011)
The finishing ration for yearling steers should contain a minimum of about 10% protein. Sorghum grain frequently contains 10% protein; this test was to determine if such sorghum grain meets protein requirements. The sorghum grain was obtained locally and had been tested for protein content at delivery during harvest. Sorghum grain testing 10.0% protein or higher was stored in one bin and that below 10% in another bin. The division was by protein testing the first load divided. A Udy analyzer (Udy Analyzer Co., Boulder, CO) was use to determine protein content of the grain. Only sorghum grain of higher protein content was used.
Keywords: Beef; Protein; Sorghum grain; Finishing ration